2007
DOI: 10.1001/archpsyc.64.8.921
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the Dopamine D4 Receptor, Clinical Outcome, and Cortical Structure in Attention-Deficit/Hyperactivity Disorder

Abstract: Context: Attention-deficit/hyperactivity disorder (ADHD) is one of the most heritable neuropsychiatric disorders, and a polymorphism within the dopamine D 4 receptor (DRD4) gene has been frequently implicated in its pathogenesis.Objective: To examine the effects of the 7-repeat microsatellite in the DRD4 gene on clinical outcome and cortical development in ADHD. We drew comparisons with a single nucleotide polymorphism in the dopamine D 1 receptor (DRD1) gene, which was associated with ADHD within our cohort, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
158
3
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(178 citation statements)
references
References 50 publications
10
158
3
5
Order By: Relevance
“…This indicates that deviance, rather than delay, characterizes the development of co-existing motor coordination problems over age in ADHD. This is contrary to older views but in accordance with more recent evidence of the (partial) persistence of structural brain abnormalities (Hall 1988;Castellanos et al 2002;Shaw 2007).…”
Section: Discussionsupporting
confidence: 70%
“…This indicates that deviance, rather than delay, characterizes the development of co-existing motor coordination problems over age in ADHD. This is contrary to older views but in accordance with more recent evidence of the (partial) persistence of structural brain abnormalities (Hall 1988;Castellanos et al 2002;Shaw 2007).…”
Section: Discussionsupporting
confidence: 70%
“…For instance, right parietal cortical normalization accompanied clinical improvement , and progressive volume loss of the inferior posterior lobes of the cerebellum accompanied persistence of ADHD (Mackie et al, 2007). Likewise, persistent ADHD is linked to a progressive loss of hippocampal volume (Shaw et al, 2007b). Stimulant drug treatment is associated with normalization of regional trajectories (Shaw et al, 2009).…”
Section: Mri Of Brain Anatomy In Atypical Pediatric Developmentmentioning
confidence: 99%
“…These delays in ADHD were most prominent in the lateral prefrontal cortex, especially the superior and DLPFC regions. In a separate study combining cortical thickness and genetics, Shaw et al (2007b) reported that possession of the dopamine D4 receptor (DRD4) 7-repeat allele in healthy children and ADHD was associated with significant cortical thinning of multiple regions including the OFC, inferior prefrontal cortex, and posterior parietal cortex. These brain regions were generally thinner in ADHD patients than in controls, although the matter is complex as ADHD patients with the 7-repeat allele fared better clinically, suggesting further study is required.…”
Section: Selected Adhd Imaging Datamentioning
confidence: 99%
“…Genetic influences on the neural circuitry of attention need to be explored further. Work has already been published that begins to link genotype and/or familial linkage with structural findings in ADHD (Casey et al, 2007a;Monuteaux et al, 2008;Shaw et al, 2007b) and to cognitive/executive function in healthy humans (Fan et al, 2003). Koten et al (2009) recently reported data from healthy twins that are very relevant to ADHD, as they showed how specific genetic factors could affect fMRI activation patterns within the brain regions of the CFP cognitive/attention network.…”
Section: Multimodal Imaging and Technique Refinementmentioning
confidence: 99%